Analisis Karakteristik Ibu Menyusui Eksklusif di Kota Pekanbaru - Fauziah, Husni; Lestari, Widia; Munawarah Tampubolon, Masrina (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Introduction: Exclusive breast milk (ASI) is breastfeeding as soon as possible after birth that is given unscheduled until the baby is 6 months old, with no food or other supplementary beverages even white water. The majority of exclusive breast coverage achievements in each region are still far below the target. The low coverage of exclusive breastfeeding is due to several factors, one of which is the characteristics of the mother. Objective: Analyze the characteristics of exclusive breastfeeding mothers in the town of Pekanbaru. Method: The sample appearance technique in this study uses the accidental sampling technique. The study was conducted in the City of Pekanbaru with the method of an offline survey of mothers who have children aged 6-12 months who succeeded in exclusive breastfeeding, sample in this study had as many as 62 respondents. Results: This study described the age range of respondents as mostly early adults aged 26 – 35 years (61.3%), most respondents are middle-educated (61,3%), the majority of respondents the mother of the household (75.8), the highest parity respondent is multi-par (58.1%), most of the type of birth respondents were normal birth (66.1%), majority of the family type respondents was Nuclear Family (53.2%), performed Early Breastfeeding Initiation (IMD) in babies as much as (58,1%), the most of those respondents came from the Minang tribe (45,2%). Conclusion: Household mothers or unemployed mothers will be more supportive of exclusive breastfeeding than working mothers.